Praktek Okultisme dalam Perspektif Alkitab : Tinjauan Teologis terhadap Dampak dan Akibat Keterlibatan dengan Okultisme (Jurnal Pendidikan Agama dan Teologi, 2025)
The increasing prevalence of occult practices within Indonesian society, including among church congregations, from a biblical theological perspective. The study employs a qualitative method, analyzing both Old and New Testament scriptures and conducting interviews with church members and leaders. Findings reveal that occultism-defined as beliefs and practices related to supernatural powers-has existed since ancient times and continues to evolve in modern society. The Bible strictly prohibits all forms of occultism, considering them abominations before God and detrimental to spiritual life. Involvement in occult practices leads to spiritual decline, disrupted relationships with God, and various spiritual and social problems. This article highlights the crucial role of the church in providing sound theological understanding and practical solutions to protect congregations from the influence of occultism.